A metal-free hydrogenation of 3-substituted 2H-1, 4-benzoxazines. Issue 34 (9th August 2016) - Wei, Simin; Feng, Xiangqing; Du, Haifeng
Abstract : A metal-free hydrogenation of 3-substituted 2 H -1, 4-benzoxazines was realized to furnish the desired products in high yields with up to 42% ee. Abstract : A metal-free hydrogenation of 3-substituted 2 H -1, 4-benzoxazines has been successfully realized with 2.5 mol% of B(C6 F5 )3 as a catalyst to furnish a variety of 3, 4-dihydro-2 H -1, 4-benzoxazines in 93–99% yields. Up to 42% ee was also achieved for the asymmetric hydrogenation with the use of a chiral diene and HB(C6 F5 )2 .